Historical biogeography of the Iberian Peninsula: multilocus phylogeny and ancestral area reconstruction for the freshwater fish genus Squalius (Actinopterygii, Leuciscidae) - Perea, Silvia (2022)
The Iberian Peninsula is one of the most ancient geological areas in Europe. Its complex orography is a consequence of several geological episodes related with two orogenic episodes that occurred from Late Devonian (Variscan orogeny) to the Cenozoic (Alpine orogeny). Unraveling the evolutionary history of strict freshwater fauna, such as leuciscid fishes, may contribute to our understanding of the paleogeographic history of a region and its configuration along time. Within the Iberian freshwater fish fauna, the genus Squalius is one of the oldest and most diversified leuciscids. Here, we used phylogenetic, phylogeographic, and ancestral area reconstruction approaches to infer relationships among Iberian drainages and the biogeographic history of these Squalius species, particularly of two of the most widely distributed species, S. carolitertii and S. pyrenaicus. Our results confirmed, in agreement with previous studies, an underestimation of the real diversity of Squalius in the Iberian Peninsula and identified divergent evolutionary lineages, highlighting the reticulate evolutionary history of the Iberian Squalius species. The ancestral reconstruction analyses indicated that several vicariance and dispersal processes occurred among different Squalius lineages, linked to the paleogeographic configuration of the Iberian Peninsula during the Cenozoic period.